Reviewing Japanese writing education at universities in Indonesia, China, and South Korea - Via Luviana Dewanty; Juju Juangsih; Ghaida Farisya (Himpunan Pengembang Kurikulum Indonesia, 2026)
Mastery of Japanese writing (sakubun) is a crucial aspect of Japanese language learning at the university level. Diverse linguistic backgrounds, cultural contexts, and writing systems pose challenges for Japanese language learners, particularly in Asian countries such as Indonesia, China, and South Korea. This study aims to highlight the problems, differences in learning models, and the use of learning media in sakubun learning in these three countries. The research method used is a systematic literature review conducted by searching academic databases for the terms